2006
DOI: 10.1111/j.1600-0404.2006.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Re-assessing the relationship between cholesterol, statins and Alzheimer's disease

Abstract: This communication integrates the purported role of cholesterol and statins in Alzheimer's disease (AD) with recent data. Meta-analysis of association studies relevant to AD indicates that apolipoprotein (apo)E4 is the only cholesterol-related polymorphism that shows clear association with AD. This suggests that the effect of apoE4 on the pathophysiology of AD occurs via a mechanism that is not directly related to cholesterol, such as fibrillization of Abeta. Despite the lack of genetic association, cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 72 publications
(123 reference statements)
0
60
0
Order By: Relevance
“…Statin treatment significantly reduces serum cholesterol but it is not clear whether statins have a direct influence on cholesterol in the central nervous system (CNS). It was reported that treatment of human subjects for 3 months with lovastatin resulted in a decrease of Aβ peptides in serum [46], whereas most clinical studies have not confirmed the effect of statins on Aβ levels in the brain [47,48]. Activation of the α-secretase and inhibition of the β-secretase require strong reduction of cellular cholesterol, therefore it is unlikely that physiological statin concentrations can influence the production of Aβ peptides in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Statin treatment significantly reduces serum cholesterol but it is not clear whether statins have a direct influence on cholesterol in the central nervous system (CNS). It was reported that treatment of human subjects for 3 months with lovastatin resulted in a decrease of Aβ peptides in serum [46], whereas most clinical studies have not confirmed the effect of statins on Aβ levels in the brain [47,48]. Activation of the α-secretase and inhibition of the β-secretase require strong reduction of cellular cholesterol, therefore it is unlikely that physiological statin concentrations can influence the production of Aβ peptides in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In order to quantify cholesterol in the samples, an internal standard made of 20 ng (51.5 pmol) of [3,[4][5][6][7][8][9][10][11][12][13] C]cholesterol was added to the collected material. For each cap, four successive extractions were carried out with 200 l of hexane.…”
Section: Cholesterol Extraction and Quantifi Cationmentioning
confidence: 99%
“…We were able to visualize the SPs using a rapid immunohistochemistry technique without pretreatment. The frozen brain sections were thawed for a few minutes at room temperature and incubated for 30 min at room temperature in a 200 l solution containing 5 g/ml of monoclonal 6F/3D antibody (specifi c for the A ␤ peptide epitope amino acids [8][9][10][11][12][13][14][15][16][17]. The samples were then washed three times for 5 min with TBS.…”
Section: Immunohistochemistry Preceding the Microdissectionmentioning
confidence: 99%
“…19,20 Very recently, results in experimental animal models showed that lower cholesterol levels slow the expression of Alzheimer's pathology, 21 and it has been reported that the intake of statins is associated with a decreased incidence of AD. 22 Furthermore, it has been shown that hypercholesterolemia accelerated AD pathology in transgenic animal models, 23 being also an early risk factor for AD in epidemiology studies. 24,25 These data point out the possibility that treating human patients with these cholesterol-lowering drugs might either reduce the risk of developing AD or help to treat it.…”
Section: Discussionmentioning
confidence: 99%